The Effect of Home Literacy on Preschoolers' Early Reading Skills: Pengaruh Literasi Rumah terhadap Kemampuan Membaca Permulaan Anak Prasekolah - Kusumawardhani, Trully; Dhieni, Nurbiana; Yetti, Elindra (Pendidikan Guru PAUD Universitas PGRI Semarang, 2025)
Abstract Early reading and writing skills, or known as early literacy, is crucial for supporting successful reading and writing during school age. Early literacy is closely related to home literacy, as the two influence each other. However, early reading skills remains low in Indonesia. Therefore, the aim of this study is to determine how home literacy affects the early reading skills of preschool children., both with or without controlling for parental age, occupation, and education. The method used in this study is a quantitative descriptive method using a multiple regression model approach. The samples in this study consist of preschool children and their parents from Little Bee Moslem Kindergarten and Al Kayyisah Kindergarten. Sampling was determined using multistage random sampling. The results of this study show that, with or without controlling for parents' age, parents' occupation, and parents' education, home literacy affects preschool children's early reading skills. All effects were equally influential, except for the impact of constraints on reading with children and the parents' occupation. Keywords: Early Reading; Home Literacy; Preschool Children Abstrak Kemampuan membaca permulaan merupakan kemampuan penting untuk menunjang keberhasilan membaca dan menulis di usia sekolah. Kemampuan membaca permulaan erat hubungannya dengan literasi rumah, karena keduanya saling memengaruhi. Namun kenyataannya, di Indonesia masih rendah kemampuan membaca permulaannya. Tujuan dari penelitian ini untuk mengetahui, bagaimana pengaruh literasi rumah terhadap kemampuan membaca permulaan anak prasekolah. Baik dengan atau tanpa mengontrol usia orang tua, pekerjaan orang tua, maupun pendidikan orang tua. Metode dalam penelitian ini menggunakan metode deskriptif kuantitatif menggunakan pendekatan model multiple regression. Sampel dalam penelitian ini berjumlah 86 dengan rincian 48 anak prasekolah dan 38 orang tua anak prasekolah TK Little Bee Moslem, TK Al Kayyisah. Penentuan sampel dengan menggunakan multistage random sampling. Hasil penelitian menunjukkan bahwa, dengan maupun tanpa mengontrol usia orang tua, pekerjaan orang tua, dan pendidikan orang tua, literasi rumah memengaruhi kemampuan membaca awal anak prasekolah. Semua pengaruhnya sama kecuali pengaruh kendala dalam kegiatan membaca bersama anak dan pekerjaan orang tua. Kata kunci: Anak Prasekolah; Literasi Rumah; Membaca Permulaan